The Use of the International Academy of Cytology Yokohama System for Reporting Breast Fine-Needle Aspiration Biopsy: A Systematic Review and Meta-analysis. Issue 2 (12th November 2022) - Nikas, Ilias P; Vey, Johannes A; Proctor, Tanja; AlRawashdeh, Mousa M; Ishak, Angela; Ko, Hyang Mi; Ryu, Han Suk
Abstract: Objectives: To perform the first meta-analysis regarding the pooled risk of malignancy (ROM) of each category of the Yokohama system for reporting breast fine-needle aspiration, as well as assess the latter's diagnostic accuracy using this new system. Methods: Two databases were searched, followed by data extraction, study quality assessment, and statistical analysis. Results: The "Insufficient, " "Benign, " "Atypical, " "Suspicious, " and "Malignant" Yokohama system categories were associated with a pooled ROM of 17% (95% CI, 10%-28%), 1% (95% CI, 1%-3%), 20% (95% CI, 17%-23%), 86% (95% CI, 79%-92%), and 100% (95% CI, 99%-100%), respectively. When both "Suspicious" and "Malignant" interpretations were regarded as cytologically positive, sensitivity (SN) was 91% (95% CI, 87.6%-93.5%) and false-positive rate (FPR) was 2.33% (95% CI, 1.30-4.14%). A summary receiver operating characteristic curve was constructed and the pooled area under the curve was 97.3%, while the pooled diagnostic odds ratio was 564 (95% CI, 264-1, 206), indicating a high level of diagnostic accuracy. When only "Malignant" interpretations were regarded as cytologically positive, the pooled FPR was lower (0.75%; 95% CI, .39%-1.42%) but at the expense of SN (76.61%; 95% CI, 70.05%-82.10%). Conclusions: Despite Yokohama's system early success, more data would be needed to unravel the system's value in clinical practice.